Electronic Fund Transfers : Compulsion or Necessity - Agrawal, Peeush Ranjan; Shukla, Sakshi Misra (Indian Journal of Computer Science, 2017)
Electronic Funds Transfers are an intrinsic and innate constituent of the banking sector. The paper envisages the unquestionable benefits that accrue from e-transfers or digital transactions. The unchallenged factors like connectivity, proper customer data, identification, security, switching gateways, and clearing houses in foreign banks operating in India were thoroughly reviewed and analyzed in the research study. The methodology of the research paper included literature review, extraction of variables, questionnaire formulation, pilot testing, data collection from primary as well as secondary resources, and application of statistical tools with the help of SPSS software. The major findings relate to the usage, concentration, comfort ability, acceptance, security, and growth of such features in the banking industry. The paper also recommends bankers to find gateways to overcome the pitfalls in electronic funds transfers and related features. Care should also be taken by customers by adhering to the processes and following of instructions correctly by service providers